2008
DOI: 10.3763/ijas.2008.0366
|View full text |Cite
|
Sign up to set email alerts
|

Developers and farmers intertwining interventions: the case of rainwater harvesting and food-for-work in Degua Temben, Tigray, Ethiopia

Abstract: Understanding the objectives, strategies and actions of the different actors that play a role in the implementation of rural development programmes is a key to explaining the latter's success and sustainability. Based on in-depth anthropological fieldwork and from an actor perspective this paper shows how the Rainwater Harvesting Pond Programme (RHPP) and the public work component of the Productive Safety Net Programme (PSNP) work out in practice in one district of the Tigray region in Ethiopia. Developers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…Sites are supposed to be selected jointly, by involving communities, but development agents (DAs) of the District Office of Agriculture together with kebelle (the lowest administrative unit in Ethiopia) administrators reportedly dominate the process. Consulting with farmers implies convincing them to implement the development programs planned by the government in federal or regional capitals [20,21]. This is partly because government sets targets (e.g., areas under area exclosure) that the district and kebelle administrators have to meet.…”
Section: Governance Of Area Exclosuresmentioning
confidence: 99%
“…Sites are supposed to be selected jointly, by involving communities, but development agents (DAs) of the District Office of Agriculture together with kebelle (the lowest administrative unit in Ethiopia) administrators reportedly dominate the process. Consulting with farmers implies convincing them to implement the development programs planned by the government in federal or regional capitals [20,21]. This is partly because government sets targets (e.g., areas under area exclosure) that the district and kebelle administrators have to meet.…”
Section: Governance Of Area Exclosuresmentioning
confidence: 99%
“…Si certains auteurs observent une réelle adaptation des communautés locales aux nouvelles injonctions (Lefort, 2012), voire un détournement allant jusqu'à capture du pouvoir (Emmenegger et al, 2011 ;Segers, 2008 ;Pausewang, 2002b), d'autres observent au contraire le maintien si ce n'est le renforcement de pratiques autoritaires qui prolongent des pratiques de pouvoir ou des représentations culturelles organisées autour de rapports de domination (Abbink, 2011), notamment concernant les relations entre l'État et la paysannerie (Dessalegn Rahmato, 2009 ;Lefort, 2010 ;Aspen, 2002, Pausewang, 2002a. L'encadrement public des espaces locaux est tel qu'il produit davantage de contrôle qu'il ne favorise le développement en raison de la forte politisation des enjeux de ce dernier (Planel, 2014).…”
Section: Glocal Ethiopia éChelles Et Repositionnements Des Pouvoirsunclassified
“…One study found disincentives for creating successful systems done by those involved in the Food for Work program and that failure helps secure employment in the program (Segers et al, 2008). Another study found the Programme is effective at protecting household food security and maintain asset levels but was not an effective mechanism to overcome poverty or result in the governmental objective of food self-sufficiency (Maxwell et al, 2013;Siyoum, 2013).…”
Section: Safety Netmentioning
confidence: 99%